Characterization of mineral content in Quercus ilex leaves by photon and neutron activation analysis (Giornale botanico italiano, 1980)
Abstract As part of a research on the holm oak stand and the Mediterranean « macchia » of Castelporziano, this study has provided the mineral characterization of Quercus ilex leaves by means of photon and neutron activation analysis. Although there is no evidence to indicate a selective distribution of the elements in the trees' crowns, some correlations are of considerable interest. Highly significant correlation coefficients are observed for the following pairs of elements: Fe-Sc, Fe-Cr, Fe-Th, Fe-Eu.
doi: 10.1080/11263508009427960